Adjusting ICT Capacity Planning by Minimizing Cyber Crime Effects in Urban Area: A System Dynamics Approach - Feldiansyah Bin Bakri Nasution; Nor Erne Nazira Bazin (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
In ICT capacity planning process, many organizations or institutions ignore unconsciously other components except statistical data of bandwidth utilization of ICT products. On this occasion, the ICT capacity planning process is analyzed by using system dynamics that considers some factors or components which are combinations between technical and non technical aspects such as: business, education, ICT infrastructure, ICT usage and cyber crime. Simulation of interrelationship between the components is conducted to understand the behavior of the system. System dynamics gives us input on correction of the statistical data by minimizing cyber crime effects. In this paper, it is also introduced the System Breakdown Structure (SBS), a technique to breakdown a big and complex system into smaller and manageable components. The objective of this SBS is to make system dynamics more expandable in hierarchy way in analyzing a system.